Toxicity of Deoxynivalenol and Its Acetylated Derivatives on the Intestine: Differential Effects on Morphology, Barrier Function, Tight Junction Proteins, and Mitogen-Activated Protein Kinases - Pinton, Philippe; Tsybulskyy, Dima; Lucioli, Joelma; Laffitte, Joëlle; Callu, Patrick; Lyazhri, Faouzi; Grosjean, François; Bracarense, Ana Paula; Kolf-Clauw, Martine; Oswald, Isabelle P. (Toxicological sciences, 2012)
The intestinal epithelium is the first barrier against food contaminants and is highly sensitive to mycotoxins, especially de oxynivalenol (DON). Consumption of DON-contaminated food is associated with outbreaks of gastroenteritis. In cereals and their byproducts, DON is present together with two acetylated derivatives, 3-ADON and 15-ADON. The aim of this study was to compare the intestinal toxicity of DON and A-DONs, using noncytotoxic doses. The toxicity was assessed using in vitro (intestinal epithelial cell line), ex vivo (intestinal explants), and in vivo (animals exposed to mycotoxin-contaminated diets) models. The effects were studied on cell proliferation, barrier function, and intestinal structure. The mechanism of toxicity was investigated by measuring the expression of the tight junction proteins and of phosphorylated ERK1/2, p38, and JNK, which are effectors of signaling pathway involved in cellular programs including embryogenesis, proliferation, differentiation, and apoptosis. On proliferating cells, 3-ADON was less toxic than DON, which was less toxic than 15-ADON. On differentiated cells, 15-ADON impaired the barrier function, whereas DON and 3-ADON did not have a significant effect. Similarly, ex vivo and in vivo, 15-ADON caused more histological lesions than DON or 3-ADON. At the molecular level, the 15-ADON activated the mitogen-activated protein kinases (MAPK) ERK1/2, p38, and JNK in the intestinal cell line, explants, and the jejunum from exposed animals at lower dose than DON and 3-ADON. Our results show that the higher toxicity of 15-DON is due to its ability to activate the MAPK. Given that cereal-based foods are contaminated with DON and acetylated-DON, the higher toxicity of 15-ADON should be taken into account.